2015
DOI: 10.1186/s12862-015-0421-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of sympatric mitonuclear variation on fitness in Drosophila subobscura

Abstract: BackgroundA number of recent studies have shown that the pattern of mitochondrial DNA variation and evolution is at odds with a neutral equilibrium model. Theory has suggested that selection on mitonuclear genotypes can act to maintain stable mitonuclear polymorphism within populations. However, this effect largely relies upon selection being either sex-specific or frequency dependent. Here, we use mitonuclear introgression lines to assess differences in a series of key life-history traits (egg-to-adult develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…In this species, variation is ubiquitous and strikingly geographically homogenous, with two dominant mtDNA haplotypes (termed I and II) typically co- occurring within populations at stable frequencies of approximately 50:50, across both the new and the old world [9, 2228]. Moreover, experimental studies have shown that the two mtDNA haplotypes are not functionally equivalent: flies that harbor these haplotypes differ in major life history traits such as metabolic rate [29], fertility [30], viability, longevity and desiccation resistance [8, 31] and two earlier studies of laboratory cage populations were able to reject genetic drift as the sole mediator of mtDNA haplotype changes [9, 32]. These observations prompted a large experimental effort by Oliver et al [33], where replicated cage populations of D. subobscura were founded by flies carrying either of the two haplotypes (at 50:50) and haplotype frequencies were then monitored for 33 generations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this species, variation is ubiquitous and strikingly geographically homogenous, with two dominant mtDNA haplotypes (termed I and II) typically co- occurring within populations at stable frequencies of approximately 50:50, across both the new and the old world [9, 2228]. Moreover, experimental studies have shown that the two mtDNA haplotypes are not functionally equivalent: flies that harbor these haplotypes differ in major life history traits such as metabolic rate [29], fertility [30], viability, longevity and desiccation resistance [8, 31] and two earlier studies of laboratory cage populations were able to reject genetic drift as the sole mediator of mtDNA haplotype changes [9, 32]. These observations prompted a large experimental effort by Oliver et al [33], where replicated cage populations of D. subobscura were founded by flies carrying either of the two haplotypes (at 50:50) and haplotype frequencies were then monitored for 33 generations.…”
Section: Resultsmentioning
confidence: 99%
“…Another, perhaps more likely, possibility is that the nuclear genetic background differed between the two studies. The nuclear background is known to, through mitonuclear epistasis, affect the relative fitness of the two haplotypes [29, 31] as well as their evolutionary dynamics [9]. …”
Section: Resultsmentioning
confidence: 99%
“…Across the species range there is high prevalence of two almost equally frequent haplotypes (named I and II) that exist together with the population specific rare ones (AFONSO et al, 1990;CASTRO et al, 1999;STAMENKOVIĆ-RADAK et al, 2012). Due to this pattern, D. subobscura has been proven as a good model species for studying evolutionary forces that shape and maintain sympatric mtDNA variation KURBALIJA NOVIČIĆ et al, 2015;JELIĆ et al, 2015). Up to now, great body of evidence shows that both adaptively neutral and selective forces shape mtDNA variation of this species.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent to which mitochondrial haplotypes exhibit sex-biases in their effects on the expression of life history phenotypes remains unclear, because relative few studies have measured phenotypic effects associated across sets of naturally-occurring mtDNA genotypes in both males and females, respectively (18, 21-23, 31-35). The sparsity of studies reporting sex-specificity in effects is particularly evident when it comes to traits tied to reproductive performance.…”
Section: Introductionmentioning
confidence: 99%